FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI MENYIMPAN HASIL PANEN PADI PETANI DI KABUPATEN SELUMA - Kusuma, Ayu Paramitha; Priyono, Basuki Sigit; Sriyoto, Sriyoto (Jurnal AGRISEP, 2015)
The purposes of this research are to 1) estimate the frequency of sale until the next harvest season, 2) examine the reasons for saving the crops of rice farmers do, 3) reveal motivation of rice farmers to store their products, and 4) analyze the factors related to the motivation of storing crops of rice farmers in the County of Seluma. The results showed that the frequency of the sale of the crops that farmers is low. Economic reasons farmers saving the crops with the largest percentage of 36,67% was to be sold again to the urgent needs and social reasons farmers save percentage with yields equal to 8.33% is there is often a relative/neighbor who borrowed. The level of motivation of farmers in storing the rice harvest is at a high percentage of category 68,33%. Non formal education factor and experience farming has a real connection with the motivation of saving crops of rice farmers in Seluma. Factors of age, formal education, land area, number of family dependants, and number of previous production doesn't have a real relationship with the motivation of storing crops of rice farmers in the County of Seluma.